Founding Editorial: Embryology — An Integrated Approach - Michael Richardson; Roger Keynes; Paula Mabee; Lynne Selwood (The Scientific World Journal)
We introduce the Embryology domain of TheScientificWorld and outline the scope and aims. We argue for an interdisciplinary approach to problems in develop-mental biology. Three areas are identified as being of particular relevance to this domain: evolutionary developmental biology, teratology, and descriptive or experimental embryology.